2014
DOI: 10.4238/2014.july.25.24
|View full text |Cite
|
Sign up to set email alerts
|

Bias toward a 1:1 ratio in primer-introduced restriction analysis PCR: mechanism and minimization

Abstract: ABSTRACT. Primer-introduced restriction analysis is widely used in molecular genetics. However, several studies have reported inconsistent data regarding sequencing, mainly among heterozygous samples. This discrepancy may be related to the bias towards a 1:1 ratio typically observed in heterozygous digestion products. In this study, we investigated the mechanism and minimization of this observed bias. Three mismatched polymerase chain reaction (PCR) models were analyzed by testing different PCR conditions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
(18 reference statements)
1
3
1
Order By: Relevance
“…When the annealing temperature lowered to 45 °C, the ratios of the PCR products were similar to that of the specific primer pair. Similar findings were reported by Denden , showing that annealing temperature is a key parameter affecting bias caused by primer mismatches.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…When the annealing temperature lowered to 45 °C, the ratios of the PCR products were similar to that of the specific primer pair. Similar findings were reported by Denden , showing that annealing temperature is a key parameter affecting bias caused by primer mismatches.…”
Section: Resultssupporting
confidence: 89%
“…These findings indicate that reducing the PCR cycle number effectively reduced the self‐annealing of the template in the later cycles of the amplification. Some investigators have also reported that the proportion of artifacts decreased at lower cycle numbers , however, the impact was less pronounced in this study. This was probably because of the majority of the artifacts were mismatch which was caused by DNA polymerase randomly (data not shown).…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations